Comparison of oxygen evolution parameters on different types of nickel hydroxide - Kotok, Valerii; Kovalenko, Vadym; Malyshev, Valerii (Eastern-European Journal of Enterprise Technologies, 2017)
A simple method for determining the oxygen evolution parameters<s>,</s> that uses stepwise potentiostatic regime was proposed. The proposed method was used to study the oxygen evolution on the nickel hydroxide samples that were prepared using different methods and had different grain size. The samples used in the research were studied using Scanning Electron Microscopy, Xray diffraction, IRspectroscopy, and Energy Dispersive Xray analysis. It was demonstrated that the used Ni(OH)2 samples have different morphology, structure and composition. The industrial βNi(OH)2 sample has a shardlike structure, high degree of crystallinity and no intercalated anions. The electrochemically prepared sample has a low degree of crystallinity and has a structure that is composed of α and βforms that contain carbonate and sulfate ions. It had been demonstrated that polarization of oxygen evolution depends on the methods of nickel (II) hydroxide synthesis and its grain size. The effective constants of the Tafel equation had been determined, which for industrial Ni(OH)2 samples are аeff=0.383 beff=0.055 (0–70 µm grain size) and аeff=0.414, beff=0.067 (0–40 µm grain size), for the electrochemically prepared sample – аeff=0.451, beff=0.089 (0–70 µm grain size). It was also demonstrated that polarization of oxygen evolution is affected differently by high current densities for different powders.